Family-Focused Treatment for Childhood Depression: Model and Case Illustrations. Issue 3 (August 2017) - Tompson, Martha C.; Langer, David A.; Hughes, Jennifer L.; Asarnow, Joan R.
Abstract: Although the evidence base for treatment of depressive disorders in adolescents has strengthened in recent years, less is known about the treatment of depression in middle to late childhood. A family-based treatment may be optimal in addressing the interpersonal problems and symptoms frequently evident among depressed children during this developmental phase, particularly given data indicating that attributes of the family environment predict recovery versus continuing depression among depressed children. Family-Focused Treatment for Childhood Depression (FFT-CD) is designed as a 15-session family treatment with both the youth and parents targeting two putative mechanisms involved in recovery: (a) enhancing family support, specifically decreasing criticism and increasing supportive interactions; and (b) strengthening specific cognitive-behavioral skills within a family context that have been central to CBT for depression, specifically behavioral activation, communication, and problem solving. This article describes in detail the FFT-CD protocol and illustrates its implementation with three depressed children and their families. Common themes/challenges in treatment included family stressors, comorbidity, parental mental health challenges, and inclusion/integration of siblings into sessions. These three children experienced positive changes from pre- to posttreatment on assessor-rated depressive symptoms, parent- and child-rated depressive symptoms, and parent-rated internalizing and externalizing symptoms. These changes were maintained at follow-up evaluations 4 and 9 months following treatment completion. Highlights: There is currently little evidence base for treatment of depressive disorders in childhood. A family-based treatment may be optimal in addressing the interpersonal problems and symptoms frequently evident among depressed children. Family-Focused Treatment for Childhood Depression (FFT-CD), a 15-session intervention, family is described in detail. Three cases illustrating the FFT-CD treatment protocol are provided and common themes/challenges in treatment are described.